A multi-strain probiotic blend reshaped obesity-related gut dysbiosis and improved lipid metabolism in obese children - Chen, An-Chyi; Fang, Tzu-Jung; Ho, Hsieh-Hsun; Chen, Jui-Fen; Kuo, Yi-Wei; Huang, Yen-Yu; Tsai, Shin-Yu; Wu, Shu-Fen; Lin, Hung-Chih; Yeh, Yao-Tsung (Frontiers in Nutrition, 2022)
Background and aims Obese children are more prone to becoming obese adults, and excess adiposity consequently increases the risk of many complications, such as metabolic syndromes, non-alcoholic fatty liver disease, cardiovascular disease, etc. This study aimed to evaluate the effects of multi-strain probiotics on the gut microbiota and weight control in obese children. Methods A double-blind, randomized, placebo-controlled trial was carried out on overweight and obese children. Subjects received 12 weeks of treatment with supplementary probiotics that contained three strains: Lactobacillus salivarius AP-32, L. rhamnosus bv-77, and Bifidobacterium animalis CP-9, plus diet and exercise guidance. A total of 82 children were enrolled, and 53 children completed the study. Results The supplementation of multi-strain probiotics resulted in a significant effect demonstrating high-density lipoprotein (HDL) and adiponectin elevation. At the same time, body mass index (BMI) and serum total cholesterol, low-density lipoprotein (LDL), leptin, and tumor necrosis factor-alpha (TNF-α) levels were reduced. Lactobacillus spp. and B. animalis were particularly increased in subjects who received probiotic supplements. The abundance of Lactobacillus spp. was inversely correlated with the ether lipid metabolism pathway, while that of B. animalis was positively correlated with serum adiponectin levels. Conclusion Our results show that obesity-related gut dysbiosis can be reshaped by the supplementation of a multi-strain probiotic to improve lipid metabolism. The regular administration of a multi-strain probiotic supplement may be helpful for weight control and health management in overweight and obese children.